1999
DOI: 10.1099/0022-1317-80-8-2041
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of rabies virus quasispecies during serial passages in heterologous hosts

Abstract: To understand the mutations and genetic rearrangements that allow rabies virus infections of new hosts and adaptation in nature, the quasispecies structure of the nucleoprotein and glycoprotein genes as well as two noncoding sequences of a rabies virus genome were determined. Gene sequences were obtained from the brain and from the salivary glands of the original host, a naturally infected European fox, and after serial passages in mice, dogs, cats and cell culture. A relative genetic stasis of the consensus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0
12

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 52 publications
4
40
0
12
Order By: Relevance
“…Therefore, truncated HN proteins might be expressed at the surface of the cells and incorporated into newly formed virus particles, possibly with consequences for the binding abilities and the infectivity of the virus (Huang et al , 2004). However, the question arises whether these aberrant and defective genomic RNAs, detected inside the infected cells, are actually packaged into the newly formed virus particles, excreted and transmitted to susceptible hosts, as shown in other models (Cabot et al , 2000;Kissi et al , 1999;Wang et al , 2003). This question could be assessed by studying the virus heterogeneity after virus purification from both organs and cloacal and tracheal swabs.…”
Section: C (1) -----------------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, truncated HN proteins might be expressed at the surface of the cells and incorporated into newly formed virus particles, possibly with consequences for the binding abilities and the infectivity of the virus (Huang et al , 2004). However, the question arises whether these aberrant and defective genomic RNAs, detected inside the infected cells, are actually packaged into the newly formed virus particles, excreted and transmitted to susceptible hosts, as shown in other models (Cabot et al , 2000;Kissi et al , 1999;Wang et al , 2003). This question could be assessed by studying the virus heterogeneity after virus purification from both organs and cloacal and tracheal swabs.…”
Section: C (1) -----------------------------------------------------mentioning
confidence: 99%
“…The missing subpopulations might then represent a memory for the quasispecies (Ruiz-Jarabo et al. , 2000) and be undetectable by the technique used, or simply have disappeared during the contact passages (Kissi et al , 1999). Each contact would need to be studied to better understand this phenomenon.…”
Section: C (1) -----------------------------------------------------mentioning
confidence: 99%
“…In addition to mutations introduced by their error-prone polymerases, RNA viruses also generate genomic variation by homologous and nonhomologous recombination and reassortment in those viruses with a segmented genome. Thus, RNA viruses exist as a heterogeneous population of closely related variants characterized by one or several dominant master nucleotide genome sequence(s) (quasispecies) (14,15,17,35). The quasispecies nature of RNA viruses confers significant adaptive potential through selection of mutants with the highest fitness in a new environment, which allows for rapid evolution (40).…”
mentioning
confidence: 99%
“…Raccoons (Smith et al, 1995), as well as bats (silver-haired and eastern pipistrelle) are the most common animals to be infected in the U.S., with bats presenting more cryptic cases of rabies infections due to a lack of obvious bite wounds (Messenger et al, 2002). Mutations of the virus through serial passes through hosts can create quasispecies, suggesting a mechanism to the accommodation to a novel hosts (Morimoto et al, 1998;Kissi et al, 1999). Bourhy et al (1999) showed, through an analysis of European strains of the virus, local genetic differentiation is taking place, facilitated by physical barriers.…”
Section: Rhabdoviridae Family: Rabies and Chandipura Virus And Austramentioning
confidence: 99%